A novel Ni Coordination Supramolecular Network hybrid monolith of 3D graphene as electrode materials for supercapacitors. (December 2017) - Yao, Hua; Zhang, Gaowei; Zhang, Feng; Li, Wei; Yang, Yangyi; Chen, Liuping
Abstract: A novel Ni-based Coordination Supramolecular Network (CSN) combining with three-dimensional reduced graphene oxide hybrid monolith (Ni-pda@3DrGO, pda = pyridine-2, 3-dicarboxylate) is fabricated by a facile one-pot surfactant-free method for the first time, and the electrochemical performances of the composite are investigated. The Ni-pda@3DrGO exhibits excellent electrochemical performance (952.85 F g −1 at 1 A g −1 ) which is much higher than that of the pure Ni-pda and the composite prepared by physically mixing. Furthermore, an asymmetric supercapacitor (ASC) is fabricated based on the Ni-pda@3DrGO and activated carbon (AC) with an energy density of 17.70 Wh kg −1 at a high power density of 1500 W kg −1 . The results demonstrate the great potentials of Ni-pda@3DrGO as electrode materials for supercapacitors. As a proof of concept, two other hybrid monoliths (Ni(quin-2-c)2 (H2 O)2 @3DrGO, Co2 (μ2 -H2 O)(na)4 ·DMF@3DrGO) have also been fabricated via the same route, implying the proposed method can be further extended to fabricate other Coordination Supramolecular Networks and 3D graphene hybrid monoliths. Graphical abstract: A Ni-based Coordination Supramolecular Network combined with Three-dimensional Reduced Graphene Oxide (Ni-CSNs@3DrGO) hybrid monolith is fabricated and investigated as electrode materials for supercapacitor. The synergy between the Ni-CSNs and interconnected graphene nanosheets realizes the composites with excellent capacitive performance. Highlights: A Ni-CSNs embedded into 3DrGO monolith is first prepared by a one-pot method. The method is expected to further fabricate analogous CSNs@3DrGO hybrid monoliths. Significantly enhanced performance is achieved after combining with 3DrGO. Electrochemical performances imply the great potentials of CSNs in energy storage.